ANALISIS SENGKETA TANAH KELUARGA ANTARA AHLI WARIS YANG MASIH MEMILIKI HAK DAN AHLI WARIS YANG SUDAH TIDAK MEMILIKI HAK - Ciko Yustio Akbar; Dinda Amalia Oktara Putri; Mochamad Ramadhan Sulaeman; Tarsis Lamhot (Cross-border, 2022)
In the distribution of inheritance, most people often experience fraud and injustice in the distribution of inheritance in disputes between brothers. This problem is the existence of heirs who no longer have rights but participate in the distribution of inheritances that are no longer entitled to them, therefore this problem is carried out using the mediation method which aims to negotiate supported by the mediator, then disputes regarding heirs and distribution must be in accordance with the regulations which applies where the land received by the heirs is valid and fair so that it can be resolved through mediation. Agreements and mediation can be done inside and outside the court. The method used in this research is descriptive analysis method. Sources of data from scientific research, observing, and going directly to the field. The theory used is the theory of justice for John Rawl. The location chosen is Kp. Tipar Cianjur, West Java because the research location is a basic dispute over nuclear family inheritance. The results of the study concluded that the dispute resolution mechanism carried out by the parties through mediation outside the judiciary was based on mutual agreement, especially in the distribution of inheritance. In this case, the distribution of the rights of the heirs over inheritance disputes over the inheritance land is carried out based on the Civil Code in order to prioritize justice, position, and equal rights between girls and boys as well as setting aside the Islamic law of the parties, because in Islamic law boys -Men are entitled to have a larger share than girls. So that the distribution of the inherited land is carried out evenly, effectively, and full of deliberation so that a harmonious kinship is established and the parties get their respective shares.